Assessing Digital Competence in Higher Education: A Gender Analysis of DigComp 2.1 Framework in Uganda - Abubakari, Mussa S; Zakaria, Gamal Abdul Nasir; Musa, Juraidah; Kalinaki, Kassim (CV. Media Digital Publikasi Indonesia, 2023)
This research paper investigated the digital competence of students in higher education in Uganda, utilising the Dig-Comp 2.1 framework as the basis for assessment. The study explores potential gender disparities in digital competence levels among students, aiming to identify areas of improvement for educational institutions and policymakers. The research utilised a quantitative approach, incorporating online surveys to collect data (N = 99) from a diverse sample of university students. Descriptive and t-test analyses were performed to analyse the significant differences in digital competencies between genders and found slight but statistically insignificant differences. The study’s findings contribute to the growing body of research on gender and digital competency and underscore the need for ongoing efforts to create inclusive and equitable digital education environments. In today's increasingly digital world, possessing adequate digital competence is crucial for personal, academic, and professional success. Higher education institutions are pivotal in equipping students with the necessary digital skills to thrive in the digital age. To enhance digital competence among all students, educators, policymakers, and institutions must focus on gender-sensitive strategies and tailor digital literacy programs to meet the diverse needs of their student population